2006
DOI: 10.2298/gsgd0602037d
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the intensity of Ljig river basin erosion: Influence of anthropogenic factor

Abstract: According to new field investigations as well as mapping of erosion in Ljig river basin we have found out that its intensity has changed in regard to period of 40 years ago. The most expressive changes were noticed in Ljig river basin. As we have not noticed changes in physical-geographical factors the cause of the intensity decrease might be only influenced by indirect anthropogenic factor. Processes of growing old and decrease of rural population, migration village-town, marginalization of agriculture and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Sustainability 2021, 13, 3130 2 of 20 Changes in agricultural land-uses in different parts of Europe and the Balkans, in the second half of the 20th century and at the beginning of the 21st century, have shown that the deintensification of land-use in agricultural areas has led to a significant reduction in sediment production and sediment transport [14][15][16][17][18]. Serbia provides such an example, where the causes of trends in soil erosion can be explained by negative demographic and socio-economic changes [19][20][21][22][23][24]. As a kind of catalyst for agricultural development, natural conditions and socio-economic characteristics are, at the same time, important factors that have contributed to the current stage of agricultural production in Serbia [25].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability 2021, 13, 3130 2 of 20 Changes in agricultural land-uses in different parts of Europe and the Balkans, in the second half of the 20th century and at the beginning of the 21st century, have shown that the deintensification of land-use in agricultural areas has led to a significant reduction in sediment production and sediment transport [14][15][16][17][18]. Serbia provides such an example, where the causes of trends in soil erosion can be explained by negative demographic and socio-economic changes [19][20][21][22][23][24]. As a kind of catalyst for agricultural development, natural conditions and socio-economic characteristics are, at the same time, important factors that have contributed to the current stage of agricultural production in Serbia [25].…”
Section: Introductionmentioning
confidence: 99%
“…This creates conditions for the frequent occurrence of torrential floods and the deposition of bed load in downstream sectors [21]. Much research at the regional [11,[22][23][24] and global scale [14,17,[25][26][27] have reported that soil erosion is significantly related to land use changes.…”
Section: Introductionmentioning
confidence: 99%
“…Geomorphological analysis of the dominant erosion processes and their intensity quantification were done in the previous researches of the Kolubara River basin [1][2][3]. The results showed that, the level of the landscape degradation and modification of geomorphologic processes by human activities has been increased in the past decades [4], and it was initiated by very fast demographic, socio-economic and technological changes in Serbia, likewise in the region [5][6][7], and in the world [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%